ULTRASTRUCTURAL CHARACTERISTICS OF INTRAMURAL GANGLION NEURONS’ OF LARGE INTESTINE AT EARLY PERIOD AFTER DISTAL RESECTION OF SMALL INTESTINE - Федорак, В.М. (World of Medicine and Biology, 2015)
Functional and morphological changes that occur in large intestine after removal of small intestine caused also changes that occur in its intramural nervous apparatus. In proposed literature it wasn’t found the data on ultrastructural changes in nervous system of large intestine’ various department after distal resection of small intestine.Objective: to establish changes in intramural apparatus’ neurons of large intestine at 7-14 days after distal resection of small intestine.Material and methods. The research was conducted on 40 white mongrel mature male rats. Collecting the material was made from caecum’ sections, large intestine and rectum for 7 and 14 days. The study was performed on material of electron microscope PfP-125 K, the accelerating voltage 75 kV, followed by a photo at increase from 3600 to 24000 times.Results and discussion. Ultrastructural at 7-th day after surgery, usually in cecum with local neurons with reduced osmiophily or its full enlightenment. They are mostly large or medium sizes, spherical or oval in shape. Their nuclei are eccentrically and uniformly, filled with a reduced number of grains of chromatin. Near nukleolema there are some clumps of heterochromatin. Perinuclear space is expanded. Organelles are diffusely in cytoplasm in comparison with other neurons. So too nerve cells with a total chromatolisys of cytoplasm. In cytoplasm of cells in places of enlightenment appears micrograin and fibrillar substance. Cysterns of Golgi complex are significantly enhanced, converted into large vacuoles. In some cells there is a collapse of their grains. Mitochondrias are swollen, their membranes and internal cristae are destroyed. Some mitochondrial inner membrane does not occur, and they turn into vacuoles. Only remnants cristae and inner membrane enable them to talk about their origin of mitochondria.At ultrastructural study neurons at 14 day more than the previous period in all parts of large intestine, especially in cecum, there are nerve cells, cytoplasm which has high electron density, with almost no free ribosomes and policy. In the cytoplasm are the remains of the complex components of the plate and ahranulyarnoyi endoplasmic reticulum. Mitochondria destroyed and almost absent, as elements of granular grid. The nucleus has an irregular shape, it becomes elongated, triangular, polygonal. Nucleoli in these cells are fragmented, poorly detected or absent. In other cells vacuoles are not merged in large cavities, but they are there in large numbers, so the light electron transparent of various size’ vacuoles and origin constitute the main background of cytoplasm.The distal small intestine resection leads to significant damage to nerve cells of nerve plexus of large intestine of rats in early stages of the experiment (7-14 days), accompanied by development of ultrastructural changes and loss of neurons. And the most pronounced changes are marked in musculo-intestinal plexus cecum, they are less noticeable as distance from it and closer to the rectum.Conclusions. In early period after distal resection of small intestine neurons in nerve plexus of large intestine, prevail ultrastructural data indicating the functional tension of organelles, degenerative changes and death of certain cells, which is most pronounced in muscle-intestinal plexus cecum.From 7-14 days of experiment in intramural nervous apparatus of large intestine prevail reactive - degenerative changes, accompanied by functional tension of structures.The prospect of further research. The results will help to establish the role of intramural nervous system of large intestine in development of compensatory restorative processes in early stages after undergoing resection of ileum, to develop a pathogenetic treatment of patients undergoing such surgery.
Keywords: distal resection of small intestine; large intestine; intramural nervous apparatus